2018
DOI: 10.1186/s12889-018-5133-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of positive mental health in Chinese adolescents

Abstract: BackgroundStudies investigating the prevalence of positive mental health and its correlates are still scarce compared to the studies on mental disorders, although there is growing interest of assessing positive mental health in adolescents. So far, no other study examining the prevalence and determinants of positive mental health in Chinese adolescents has been found. The purpose of this study was to assess the prevalence and correlates of positive mental health in Chinese adolescents.MethodsThis cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 64 publications
12
51
1
2
Order By: Relevance
“…The results of this study show that the mediating effects of negative emotions and resilience may contribute to understanding the relationship between teacher support and mental well-being in a sample of Chinese adolescents. First, consistent with a prior study (Guo et al, 2018), we found that teacher support was a significant predictor of mental well-being. Together, this indicates that adolescents who receive more care and help from teachers tend to have a high level of mental well-being.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study show that the mediating effects of negative emotions and resilience may contribute to understanding the relationship between teacher support and mental well-being in a sample of Chinese adolescents. First, consistent with a prior study (Guo et al, 2018), we found that teacher support was a significant predictor of mental well-being. Together, this indicates that adolescents who receive more care and help from teachers tend to have a high level of mental well-being.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, some studies found that support from teachers has a positive influence on adolescent psychological well-being, mental health, happiness, and satisfaction (Lau et al, 2010;Wang et al, 2014;Alivernini et al, 2019). Although many studies have demonstrated the association between teacher support and mental illness, such as depression (Pössel et al, 2018) and anxiety (Zhao and Li, 2017), only a few studies have explored the positive association between teacher support perceived by middle school students and positive mental health (Guo et al, 2018). More importantly, the mechanism underlying these protective resources and positive outcomes has yet to be identified.…”
Section: The Relationship Between Teacher Support and Mental Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity is essential for optimal health and development in children and can positively contribute to prevention of excess weight gain, 1 cognitive performance, 2 motor development 3 and psychosocial health. 4 Modes of physical activity that often create beneficial moderate-to-vigorous physical activity (MVPA) include sports participation, 5 6 active transport 7 and outdoor recreation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are benefits for mental health among individuals who have higher levels of trust. For instance, substantial evidence from the literature indicates that a higher level of trust is associated with better mental health and lower level of distress (Abbott and Freeth 2008;Fahmi et al 2019;Guo et al 2018;Sato et al 2018). Also, the literature suggests that people who have trust towards others are happier than those without trust (Tokuda et al 2010).…”
Section: Semmentioning
confidence: 99%